The Influence Of Self Efficacy and Locus Of Control On Employee Performance Through Learning Agility at PT. Pegadaian in Cirebon - Rachman, Nisa; Ningsih, Imas Ayu; Hartono, Edy (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Learning agility and its impact on performance at PT Pegadaian are the focus of this study, which aims to investigate the function of self-efficacy and locus of control in this context.  There were no exceptions among the 120 workers; everyone was actively engaged.  Results showed a favorable correlation between high levels of self-efficacy and better performance.  In a similar vein, having an internal locus of control helps one function at their best.  The link between self-efficacy, locus of control, and employee performance was strengthened by learning agility, a major mediating variable.  To overcome the impact of these two mental aspects on productivity on the job, people's capacity for rapid and flexible learning is crucial.  As a result, boosting employees' learning agility and positive self-efficacy may work hand in hand to boost their performance. This study investigates the mediating role of learning agility in the relationship between self-efficacy, locus of control, and employee performance at PT. Pegadaian in Cirebon. A total of 120 employees participated in the study using a saturated sampling technique. Data were collected through questionnaires and analyzed using SPSS 25. The findings reveal that self-efficacy (β = 1.000, p < 0.000) and locus of control (β = 0.176, p < 0.000) significantly affect employee performance. Learning agility acts as a significant mediator, with a direct effect on performance (β = 0.501, p < 0.000), indicating its pivotal role in enhancing performance through psychological traits. The adjusted R² value of 1.000 supports the robustness of the model. These findings underscore the importance of internal psychological mechanisms and adaptability in achieving high job performance.